Safety and Immunogenicity of a Mycoplasma ovipneumoniae bacterin for domestic sheep (Ovis aries). - Jessie C Ziegler (Public Library of Science (PLoS), 2014)
Background Mortality from epizootic pneumonia is hindering re-establishment of bighorn sheep populations in western North America. Mycoplasma ovipneumoniae, a primary agent of this disease, is frequently carried asymptomatically by the domestic sheep and goats that constitute the reservoir of this agent for transmission to bighorn sheep. Our long-term objective is to reduce the risk of M. ovipneumoniae infection of bighorn sheep; one approach to this objective is to control the pathogen in its reservoir hosts. Methods The safety and immunogenicity of M. ovipneumoniae for domestic sheep was evaluated in three experimental immunization protocols: 1) live M. ovipneumoniae (50 ug protein); 2) killed M. ovipneumoniae (50 ug whole cell protein) in oil adjuvant; and 3) killed M. ovipneumoniae (250 ug whole cell protein) in oil adjuvant. Immunogenicity was assessed by two serum antibody measures: competitive enzyme-linked immunosorbent assay (cELISA) (experiments 1-3) and serum growth inhibition (Experiment 3). Passive immunogenicity was also assessed in the third experiment using the same assays applied to blood samples obtained from the lambs of immunized ewes. Results and conclusions Adverse reactions to immunization were generally minor, but local reactions were regularly observed at immunization sites with bacterins in oil adjuvants. No evidence of M. ovipneumoniae specific antibody responses were observed in the first or second experiments and no resistance to colonization was observed in the first experiment. However, the ewes in the third experiment developed strong cELISA serum antibody responses and significant serum M. ovipneumoniae inhibition activity, and these responses were passively transferred to their lambs. The results of these trials indicate that immunization with relatively large antigenic mass combined with an adjuvant is capable of inducing strong active antibody responses in ewes and passively immunizing lambs.